A Finite Equational Base for CCS with Left Merge and Communication Merge - Aceto, Luca; Fokkink, Willem Jan; Ingólfsdóttir, Anna; Luttik, Bas (BRICS Report Series, 2006)
Using the left merge and communication merge from ACP, we present an equational base for the fragment of CCS without restriction and relabelling. Our equational base is finite if the set of actions is finite.